Brain delivery of intranasal in situ gel of nanoparticulated polymeric carriers containing antidepressant drug: behavioral and biochemical assessment. (April 2015) - Kaur, Prabhjot; Garg, Tarun; Vaidya, Bhuvaneshwar; Prakash, Atish; Rath, Goutam; Goyal, Amit K.
Abstract This study was aimed for brain delivery of Tramadol HCl (centrally acting synthetic opioid) following intranasal administration for treatment of depression. Chitosan nanoparticles (NPs) were prepared by ionic gelation method followed by the addition of developed NPs with in the Pluronic and HPMC-based mucoadhesive thermo-reversible gel. Developed formulation optimized based on the various parameters such as particle size, entrapment efficiency, in vitro release study. Depression induction was done by forced swim test and evaluated by various behavioral and biochemical parameters. Furthermore, results showed significantly increased in locomotors activity, body weight as compared to control group. It also showed alteration in biochemical parameters such glutathione level and catalase levels significantly increased other than lipid peroxidation and nitrite level was found to be decreased after intranasal administration of formulation. Thus, intranasal TRM HCl NP-loaded in situ gel was found to be a promising formulation for the treatment of depression.